2023
DOI: 10.3390/curroncol30060419
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Disease Progression to Upfront Pembrolizumab Monotherapy in Advanced Non-Small-Cell Lung Cancer with High PD-L1 Expression Using Baseline CT Disease Quantification and Smoking Pack Years

Abstract: Health Canada approved pembrolizumab in the first-line setting for advanced non-small-cell lung cancer with PD-L1 ≥ 50% and no EGFR/ALK aberration. The keynote 024 trial showed 55% of such patients progress with pembrolizumab monotherapy. We propose that the combination of baseline CT and clinical factors can help identify those patients who may progress. In 138 eligible patients from our institution, we retrospectively collected their baseline variables, including baseline CT findings (primary lung tumor size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…These findings highlight the favorable EFS observed with pembrolizumab treatment, and are consistent with the observations from most of perioperative trials including CheckMate-816, IMpower010, and KEYNOTE-091 ( 1 , 3 , 4 ) confirming the efficacy of ICIs in reducing disease recurrence or progression. The KN671 trial demonstrated clear EFS benefit across various subgroups with the exception of never smokers and patients with programmed cell death ligand 1 (PD-L1) <1%, who may not achieve as durable of a response compared to current or former smokers, and patients with positive PD-L1 expression, in line with previous findings ( 11 , 12 ). Regarding overall survival (OS), the estimated OS at 24 months was 80.9% in the pembrolizumab group and 77.6% in the placebo group with a P=0.02, which did not meet the significance criterion based on predetermined statistical thresholds.…”
supporting
confidence: 82%
“…These findings highlight the favorable EFS observed with pembrolizumab treatment, and are consistent with the observations from most of perioperative trials including CheckMate-816, IMpower010, and KEYNOTE-091 ( 1 , 3 , 4 ) confirming the efficacy of ICIs in reducing disease recurrence or progression. The KN671 trial demonstrated clear EFS benefit across various subgroups with the exception of never smokers and patients with programmed cell death ligand 1 (PD-L1) <1%, who may not achieve as durable of a response compared to current or former smokers, and patients with positive PD-L1 expression, in line with previous findings ( 11 , 12 ). Regarding overall survival (OS), the estimated OS at 24 months was 80.9% in the pembrolizumab group and 77.6% in the placebo group with a P=0.02, which did not meet the significance criterion based on predetermined statistical thresholds.…”
supporting
confidence: 82%